PERIKOP ANAK YANG HILANG (LUK 15:11-24) DALAM PERSPEKTIF HIERARKI NILAI MAX SCHELER DAN RELEVANSI PADA ZAMAN SEKARANG - Babtista, Thomas Rosario (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
In this day and age of instant gratification, many people weigh a decision by the value of enjoyment. Obviously, this kind of judgment is very superficial and artificial. Judgment should be based on noble values. In his hierarchy of values theory, Max Scheler suggests that there are four hierarchies of values, namely the value of pleasure, the value of life or vitality, spiritual value, and the value of holiness. The lowest hierarchy is pleasure value and the highest is holiness value. This value must exist in life, as it is the meaning behind actions. This can be seen in “the parable of the Prodigal Son” (Lk 15:11-24) told by Jesus to the tax collectors and sinners. There is a hierarchy of values revealed in the characterizations and inner journeys of the characters. By exploring the text of Luke 15:11-24 and juxtaposing it with Max Scheler's hierarchy of values theory, the author hopes to help everyone in this instant age to consider things more from the most noble values. There are two methods used in writing this text, namely literature study and hermeneutics. This method is expected to help the author in analyzing and interpreting the text in detail and holistically. Broadly speaking, the author found that the character of the Youngest Child experienced an increase in the appreciation of values, starting from the value of pleasure, to spiritual values. The text closes with the appreciation of the value of holiness by the Father. In other words, this text provides a complete appreciation of values from Max Scheler's hierarchy of values.